Targeting Biomarkers of Proliferation and Inflammation (Ki67, p53, and COX-2) in Actinic Keratoses with Photodynamic Therapy - Justyna Ceryn; Aleksandra Lesiak; Magdalena Ciążyńska; Dorota Sobolewska-Sztychny; Marcin Noweta; Olga Stasikowska-Kanicka; Karol Ciążyński; Iris Zalaudek; Joanna Narbutt (Biomedicines, 2025)
Background: Actinic keratoses (AKs) are common pre-neoplastic lesions that may progress to cutaneous squamous cell carcinoma (cSCC). Photodynamic therapy (PDT) is an effective field-directed treatment for AK, but its impact on key biomarkers remains unclear. This study evaluates the clinical, dermatoscopic, and immunohistochemical effects of PDT on AK, with a focus on proliferation (Ki67, p53) and inflammation (COX-2) markers, to assess its efficacy in delaying carcinogenesis. Methods: In our prospective one-center study, we enrolled 31 patients with AK, with no history of previous AK treatment. They underwent three PDT sessions at four-week intervals, with follow-up eight weeks after the final session. Clinical, dermatoscopic, and immunohistochemical analyses of Ki67, p53, and COX-2 expression were performed before and after treatment. Results: Clinically, 54.8% of patients achieved complete lesion clearance, with no residual severe AK lesions. Ki67 and p53 immunoexpression significantly decreased post-PDT (p < 0.05), confirming its antiproliferative effect. COX-2 expression also declined significantly (p < 0.05), supporting PDT’s anti-inflammatory role. However, COX-2 remained stable or increased in 35.48% of cases, possibly due to inflammation-induced regeneration. There is a positive correlation between the reduction in Ki67, p53, and COX-2 immunoexpression and the decrease in AK severity (both according to Olsen grade and dermatoscopic grade). Conclusions: PDT effectively reduces AK severity, proliferation, and inflammation markers, potentially delaying carcinogenesis. However, residual biomarker expression suggests that additional treatment sessions or combination therapies may be necessary for complete lesion clearance. Further studies are required to optimize PDT protocols.